GAMBARAN PELAKSANAAN UPAYA PENCEGAHAN PENYEBARAN COVID-19 MELALUI PROTOKOL KESEHATAN DI DESA KEDUNG WONOKERTO RW.04 KECAMATAN PRAMBON KAB. SIDOARJO PERIODE MARET 2021 - merry patrinila (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2022)
Abstrack At the end of 2019 the world having a slump because emergence of a new virus called COVID-19. Limiting activities outside the home is also carried out to anticipate and reduce of amount patients with COVID-19 in the Indonesia. the purpose of this research is to know how to prevention the spread of the virus COVID-19 in the Kedungwonokerto village of hamlet 4 Sub-district Prambon District Sidoarjo. This types of the research use research method descriptive qualitative on 291 people through random sampling. This research use questionnaire for submit the data and for qualitative analysis with present the variable frequency distribution. The result of the analysis is implementation to prevention the spread of the virus COVID-19 includeing category quite well with category presentation 67%. Implementation distribution prevention the spread of society have done implement prevention the spread of virus COVID-19 appropriate with health protocol for purpose to breaking the virus COVID-19. Keywords: Prevention, Spread, COVID-19